KEDUDUKAN SAKSI DALAM PEMBUATAN AKTA JUAL BELI HAK ATAS TANAH DI HADAPAN PEJABAT PEMBUAT AKTA TANAH - Yudhi Aditya Putra, Kadek; R., Ibrahim; Sarna, Kadek (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 06, September 2013)
Considering State Indonesia is Agricultural Country and most its society have subsistence of agricultural produce, hence increasing also requirement of land; ground human being will till often we meet the existence of land; ground sales transaction. In this case, such land; ground in congeniality of yuridis of is socalled rights. Such as those which we know, in land; ground sales transaction to get authenticity about ownership of hence require to be made by an made agreement before Functionary of Maker of Act of land. Purchasing and selling agreement happened caused by second agreement split side, good regarding object which is sold and also his price. Related of solution in this research, namely responsibility a eyewitness in making of sale act buy, land right before Functionary Of Maker of Act of land (PPAT) and authenticity from an sale act buy land; ground if when related to domicile eyewitness.
Keywords: Act of land, eyewitness, Functionary Of Maker of Act of land (PPAT), sales